2012
DOI: 10.1128/jvi.06900-11
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Transformation Tropism Exhibited by Human T Lymphotropic Virus Type 1 (HTLV-1) and HTLV-2 Is the Result of Postinfection T Cell Clonal Expansion

Abstract: e Human T lymphotropic virus type 1 (HTLV-1) and HTLV-2 are related but pathogenically distinct viruses. HTLV-1 mainly causes adult T cell leukemia, while HTLV-2 is not associated with leukemia. In vitro, HTLV-1 and HTLV-2 predominantly transform CD4؉ and CD8 ؉ T cells, respectively: the genetic determinant maps to the viral envelope. Herein, we investigate whether this transformation tropism occurs during initial infection or subsequently during the cellular transformation process. Since most individuals are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 49 publications
7
48
0
Order By: Relevance
“…5B). Along with the fact that thymic CD8 and CD4 T cells had similar PVLs, this observation implies a much smaller expansion of infected CD8 T cells in the periphery than of CD4 T cells, an observation in agreement with a previous report showing that HTLV-1's in vivo tropism is a consequence of predominant expansion of peripheral CD4 over CD8 T cells (27).…”
Section: Resultssupporting
confidence: 80%
“…5B). Along with the fact that thymic CD8 and CD4 T cells had similar PVLs, this observation implies a much smaller expansion of infected CD8 T cells in the periphery than of CD4 T cells, an observation in agreement with a previous report showing that HTLV-1's in vivo tropism is a consequence of predominant expansion of peripheral CD4 over CD8 T cells (27).…”
Section: Resultssupporting
confidence: 80%
“…Our previous longitudinal phenotype analysis of HTLV-immortalized in vitro cultures revealed that HTLV-1 and HTLV-2 induced the proliferation of both CD4 ϩ and CD8 ϩ T cells in the initial weeks postcoculture (33). However, after 4 to 5 weeks, the preferred T cell population emerged via selection and clonal expansion (33). These results, taken together with results in this study, led us to hypothesize that the SU1 protein expressed in HTLV-infected cells might interact with host cellular factors to mediate the preferential clonal expansion of CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 49%
“…This result is consistent with our recent in vivo study, which clearly confirms that HTLV-1 and HTLV-2 do not exhibit any CD4 ϩ or CD8 ϩ T cell preference at the infection stage. Those studies also showed that the T cell predominance emerged only after 4 to 5 weeks of coculture, providing strong evidence that the observed preferential tropism is not determined by the initial infection of the cell but by later interactions of the envelope with the infected cell (33).…”
Section: Discussionmentioning
confidence: 85%
“…Taken together, our results suggested that studies comparing HBZ and APH-2 should be performed and the results should be interpreted carefully, given that the relative abundance of APH-2 is much lower than that of HBZ in natural infection. The primer pairs used for the specific detection of viral mRNA species were described previously (45,46). Data from triplicate experiments are presented in histogram form with means and standard deviations.…”
Section: Discussionmentioning
confidence: 99%
“…For each run, standard cDNA, sample cDNA, and a notemplate control were all assayed in triplicate. The reaction conditions were 95°C for 5 min, followed by 40 cycles of 94°C for 30 s, 56°C for 30 s, and 72°C for 45 s. Primer pairs for the specific detection of viral mRNA species (gag/pol, tax/rex, hbz, aph-2), platelet-derived growth factor beta polypeptide (pdgfb), and human glyceraldehyde-3-phosphate dehydrogenase (hgapdh) were described previously (45)(46)(47). Data from triplicate experiments are presented in histogram form as means with standard deviations.…”
Section: Methodsmentioning
confidence: 99%